DAMPAK PELAKSANAAN HOMA JNANA PADA KOMUNITAS BAHUNG TRINGAN, BEBANDEM, KARANGASEM - Suwantana, I Gede (Institut Hindu Dharma Negeri Denpasar, 2018)
Homa Jnana organized by Bahung Tringan Community, Bebandem Village, Karangasem is an ancient ritual that was revived as a medium of spiritual journey of the community, especially members of the community. This ritual is very simple, but has an infinite impact esoterically. Based on the practitioners? experience, there were several effects that were directly felt by them. Physical and mental health problems, community peace and environmental problems are directly affected by the implementation of Homa. People can recover from their illness and the mind can calm down when following Homa. Through the positive vibrations that are propagated, this ritual is able to give a positive influence to the minds of the people or communities around the Homa implementation site. Likewise the atmosphere is purified around the practice of Homa from various types of pollution, especially pollution caused by the mind. This article describes in full the immediate impact felt by the community who are actively participating in the Homa ritual periodically.